SignalPlant: an open signal processing software platform - Plesinger, F; Jurco, J; Halamek, J; Jurak, P (Physiological measurement, 2016)
The growing technical standard of acquisition systems allows the acquisition of large records, often reaching gigabytes or more in size as is the case with whole-day electroencephalograph (EEG) recordings, for example. Although current 64-bit software for signal processing is able to process (e.g. filter, analyze, etc) such data, visual inspection and labeling will probably suffer from rather long latency during the rendering of large portions of recorded signals. For this reason, we have developed SignalPlant-a stand-alone application for signal inspection, labeling and processing. The main motivation was to supply investigators with a tool allowing fast and interactive work with large multichannel records produced by EEG, electrocardiograph and similar devices. The rendering latency was compared with EEGLAB and proves significantly faster when displaying an image from a large number of samples (e.g. 163-times faster for 75  ×  10(6) samples). The presented SignalPlant software is available free and does not depend on any other computation software. Furthermore, it can be extended with plugins by third parties ensuring its adaptability to future research tasks and new data formats.
Keywords: časové faktory; Software; software; Electroencephalography; Signal Processing, Computer-Assisted; počítačové zpracování signálu; přístup k informacím; internet; Access to Information; Internet; elektroencefalografie; Time Factors; Electrocardiography; elektrokardiografie